Low Complexity Wireless Powered Information Transfer Strategy for Multiuser MIMO Systems - Jihoon Choi; Jingon Joung (IEEE Access, 2018)
In this paper, the minimum achievable rate maximization problem for wireless-powered multiple users is investigated. Zero-forcing (ZF)-based precoding is considered for information transmission (IT) in the uplink from multi-antenna users to a multi-antenna access point that charges the users through wireless power transmission (PT) in the downlink. A max–min user rate optimization problem is formulated when a ZF-based transmission is used for spatial division multiplexing in the IT phase. We propose a low-complexity method to design the energy beamformer for the PT phase, the transmit power allocation for multi-stream transmission for the IT phase, and the time ratio between PT and IT phases in terms of maximizing the minimum achievable rate. The validity of the proposed scheme is shown through complexity analysis and numerical simulations.